Encampment time : an anthropological analysis of the land occupations in Brazil - Loera, Nashieli Cecília Rangel [UNESP] (Taylor & Francis, 2010)
In this article the social trajectory of a land occupation participant, an encamped woman (Edesmaria) who is a member of an extended landless family, is closely examined in order to demonstrate the inner workings of what is called 'the world of land occupations' in Brazil. Through a native expression (encampment time), it is demonstrated that nowadays, for some individuals, involvement in land occupations and landless workers' movements represents not just an opportunity to claim a parcel of land, but, even more importantly, a chance for social mobility and recognition. In this sense, encampment time is a social code and, as such, it not only quantifies the amount of time spent in a given encampment, but it is also a marker of prestige and status as well as a principle that organises and orders social relations in the land occupation world.
Keywords: landless movements; camps; encampment time; world of land occupations